Delegitimation of single-mux policy on re-regulation process of Indonesian broadcasting bill in media framing - Kalaloi, Abdul Fadli (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to explain the reality behind the framing of negative coverage of the single-mux policy in the re-regulation of Law No.32/2002, from a more macro perspective. Framing negative news by building reader cynicism on the single-mux policy option is associated as one of the efforts to delegitimize the single-mux policy, throughout the process of discussing the policy in Parliament. This research links the reality between negative news framing around single-mux policy options, with the media agenda in the broadcast industry in Indonesia. The author used the concept of framing-strategy analysis Cappella and Jamieson (1997) as an analysis tool, to analyze data from detikcom content as online news media around the debate on single-mux and multi-mux policies on 2017-2018 reporting period. The results identified that the media developed a negative narrative about single-mux policies aimed to rise public cynicism about the policy. Cynicism is built by constructing issues around singlemux policies with policy impacts that conflict with democratic values, such as mass layoffs in the broadcasting industry, the issue of excesses of authoritarian policies because management rights are controlled solely by the government, to the issue of unpreparedness of government infrastructure which results in a waste of budget in the process of procuring new infrastructure. These facts the author associates with the effort to delegitimize single-mux policy options in the legislation process, using the arguments of Berger, Ridgeway, Fisek and Norman, (1998).